Investigating the Role of FlhF Identifies Novel Interactions With Genes Involved in Flagellar Synthesis in Campylobacter jejuni - Li, Xiaofei; Ren, Fangzhe; Cai, Guoqiang; Huang, Pingyu; Chai, Qinwen; Gundogdu, Ozan; Jiao, Xinan; Huang, Jinlin (Frontiers in Microbiology, 2020)
FlhF is a key protein required for complete flagellar synthesis, and its deletion results in the complete absence of a flagella and thus motility in Campylobacter jejuni. However, the specific mechanism still remains unknown. In this study, RNA-Seq, EMSAs, ChIP-qPCR and β-Galactosidase assays were performed to elucidate the new role of FlhF in flagellar synthesis. Results showed that FlhF has an overall influence on the transcription of flagellar genes with an flhF mutant displaying down-regulation of most flagellar related genes. FlhF can directly bind to the flgI promoter to regulate its expression, which has significant expression change in flhF mutant. The FlhF-binding site in the flgI promoter was also discovered. Meanwhile, FlhF can directly bind to the promoters of rpoD, flgS and fliA encoding early flagellin regulators, thereby directly or indirectly regulating the synthesis of class I, II and III flagellar genes, respectively. Collectively, this study demonstrates that FlhF may directly regulate the transcription of flagellar genes by binding to their promoters as a transcriptional regulator, which will be helpful in understanding the mechanism of FlhF in ﬂagellar biosynthetic and bacterial ﬂagellation in general.